Assessing the sensitivity of leeches as indicators of water quality - Cortelezzi, Agustina (2017)
The objective of this work was assessing the sensitivity of leeches to several water quality attributes in lowlands streams.Weused occupancymodelling that account explicitly for detectability, to estimate the influence of four variables (dissolved oxygen, 5-days biochemicals oxygen demand, conductivity, and dissolved inorganic nitrogen) affecting nine species. We described the sensitivity as a change in the occupancy along the range of water quality attributes.We found at least one species of Helobdella in 81% of sites and Helobdella, as genus, was detected along the entire gradient of each attribute. However, differences in the sensitivitywere observed between species. For example, if we analyse the sensitivity of the genus Helobdella to dissolved oxygen, we can say that it is very tolerant. However, if we analyse the response to dissolved oxygen of each one of the species of Helobdella,wewill realize that H. michaelseni, and H. simplex showed a high occupancy at high levels of dissolved oxygen; while H. hyalina and H. triserialis lineata showed high occupancy at low levels. Describe the sensitivity of the species in terms of occupancy, offers a new methodology to understand how the species behave along a stressor gradient.